WORKING MEMORY INDEX AS A LINKING CONSTRUCT BETWEEN WAIS-IV AND EXECUTIVE FUNCTION: A LITERATURE REVIEW 2021–2026 - Natalia Susanti, Ruth (Jurnal Riset Multidisiplin Edukasi, 2026)
This study examines the conceptual and empirical relationship between the Wechsler Adult Intelligence Scale–Fourth Edition (WAIS-IV) and executive function within a contemporary neurocognitive framework. A qualitative descriptive literature review was conducted by systematically collecting and synthesizing peer-reviewed studies published between 2021 and 2026. Literature was identified through Google Scholar and Taylor & Francis Online using keywords related to WAIS-IV, executive function, working memory, and cognitive control. Selected articles were analyzed using narrative synthesis to identify consistent patterns linking WAIS-IV indices to executive function components. The findings indicate that the Working Memory Index (WMI) represents the most consistent operational link between intelligence and executive control, particularly in attentional regulation and information manipulation. However, executive functioning in real-life contexts involves broader regulatory mechanisms that extend beyond structured intelligence testing conditions. The novelty of this review lies in positioning working memory as a partial mediator while clarifying the conceptual distinction between global IQ scores and adaptive executive regulation. The study highlights the importance of integrating executive function assessment into educational and clinical decision-making processes to avoid overreliance on Full Scale IQ scores.